Legal Categorization and Implications of the Placement of the Notary Profession in the Indonesian Standard Business Classification - Anugrah Haryata Pratama (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2023)
Article 1 point 1 of Law Number 30 of 2004 concerning the Office of a Notary Public explains that a Notary is a public official authorized to make authentic deeds in accordance with the Law on the Position of a Notary Public and other laws. From the other side, the regulation of the Head of the Central Bureau of Statistics Number 2 of 2020 concerning the Indonesian Standard Business Classification whose purpose is to classify economic activities in Indonesia states that Notaries are categorized together with other business actors in code 69104. Mention of Notaries in Indonesian Standard Business Classification's efforts to make Notaries able to move into entrepreneurs in accordance with the title of classification number 69104